2020
DOI: 10.1109/jiot.2019.2957314
|View full text |Cite
|
Sign up to set email alerts
|

FESDA: Fog-Enabled Secure Data Aggregation in Smart Grid IoT Network

Abstract: With advances in Fog and edge computing, various problems such as data processing for large Internet of things (IoT) systems can be solved in an efficient manner. One such problem for the next generation smart grid IoT system comprising of millions of smart devices is the data aggregation problem. Traditional data aggregation schemes for smart grids incur high computation and communication costs, and in recent years there have been efforts to leverage fog computing with smart grids to overcome these limitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(48 citation statements)
references
References 34 publications
(100 reference statements)
0
48
0
Order By: Relevance
“…Multiple authors have suggested the embedding of deep learning techniques to improve the security in IoT-based Localization applications [ 98 , 99 , 100 ]. Additionally, encryption algorithms and digital signatures using public and private keys can improve the resilience against external attacks [ 101 , 102 ]. However, the extent of security by using minimal resources is still a big challenge.…”
Section: Future Directionsmentioning
confidence: 99%
“…Multiple authors have suggested the embedding of deep learning techniques to improve the security in IoT-based Localization applications [ 98 , 99 , 100 ]. Additionally, encryption algorithms and digital signatures using public and private keys can improve the resilience against external attacks [ 101 , 102 ]. However, the extent of security by using minimal resources is still a big challenge.…”
Section: Future Directionsmentioning
confidence: 99%
“…Offloading by the vehicles to MEC/cloud servers is done through the RSU. The authors of [28,59,60] also use a similar system model in their work. In [33], authors consider a model which uses neither edge devices nor cloud servers but edge-cloud devices in their system model.…”
Section: Cloud Computingmentioning
confidence: 99%
“…There is also trustworthiness issue related to security and privacy of data in cloud storage scenarios, there may arise a security concern due to continuous connectivity of IoT-based sensors with the edge entities [7,8], the vulnerabilities can arise specially in sectors like healthcare where a small change in values can be life threatening. Data aggregation is also termed as one big problem for smart grid IoT systems [9] which is somewhere related to data gathering and management issue. Some applications are delay sensitive due to challenges when processing a large amount of data at edge or the cloud level of devices, leading to latency, which is not acceptable in some critical applications like health scenarios, transport management, etc.…”
Section: Introductionmentioning
confidence: 99%